Philosophy 167: Class 7 - Part 10 - The Ski-Jump Experiment: the Perfect Empirical Test, Suppressed. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Describes Galileo's Ski-Jump Experiment demonstrating the parabolic shape of a ballistic trajectory.; Opening line: "All right, what I wanna do now is turn to Galileo's own test of this theory."; Duration: 16:13 minutes.; Segment: Class 7, Part 10.